Embriogênese somática de cana-de-açúcar: uma revisão bibliográfica - Sanchez, Amanda Dutra (Universidade Federal de São Carlos, 2024)
Sugarcane (Saccharum officinarum) is one of the most produced and used around the world, especially in Brazil. However, this high demand can generate challenges in production, motivating research groups to explore genetic modifications to optimize sugarcane production. This Thus, the objective of this work is to carry out a bibliographical review on the use of Embryogenic calluses in genetically modified sugarcane. To assist In this review, the works found come from searches on platforms Capes and Google Scholar periodicals, listing works that were compatible with the theme. From this, it is notable that Brazil has many places that are difficult to sugarcane production, whether due to climate change such as high temperatures, rainfall or infertile soil problems. In this context, genetic modifications emerge as a promising alternative to maintain production and sustain the economy. -THE micropropagation, via the production of embryogenic callus, is an essential tool in this process, allowing large-scale multiplication and the choice of genotypes of high performance for the genetic improvement of sugar cane. Therefore, studies conducted by Embrapa, Ridesa, CTC and IAC are essential on this path, aiming to understand sugarcane, its genotypes and optimizing the production of this crop.
Somatic embryogenesis of sugarcane: a review bibliographic
Keywords: Cana-de-açúcar; Modificação genética; Calos embriogênicos; Transformação genética; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA